퍼지-트랩 기체크로마토그래프/질량분석계에 의한 물시료 중 Trihalomethanes의 분석 및 위해성 평가 - 곽선영; 표희수; 박송자 (환경독성보건학회, 2005)
Recently, significant contamination problems by residual chemicals have occasionally been occurred frommajor rivers and drinking water in Korea. Therefore, the management for use of them and risk assessmentshould be more strictly performed. In this study, we have analyzed trihalomethanes in treated water samplestaken from water plants located in the region of four major rivers (i.e. Han river, Geum river, Youngsan riverand Nakdong river) in Korea for eight years (1997~ 2004). From the data, we could assess the excess cancerrisk by calculating the chronic daily intakes (CDI) multiplied by individual oral slope factors, Q1*, for thecancer suspected matters such as trihalomethanes, moreover the hazard index which is calculated by dividingthe CDI by the acceptable daily reference dose(RfD) was determined for the risk assessment. As a result, in thecase of 95 percentile excess cancer risk, it was shown that the excess cancer risk for dichlorobromomethane inthe Nakdong river region is highest among the tested samples as 8.73× 10-6. The 95 percentile total hazardindex (the sum of individual hazard indices considering RfD), in addition, was below 1.0 for all samples, andtherefore it was assessed that water samples taken from treatment plants of four major rivers are not harmful.